PENGARUH CUSTOMER EXPERIENCE TERHADAP PEMBELIAN ULANG DI MIHAR STORE PANDEGLANG DENGAN ONLINE BRAND COMMUNITIES DAN POSITIF ELECTRONIC WORD OF MOUTH SEBAGAI VARIABEL MEDIASI - Pamungkas, Lita Budiarti; Handoko, Pryo; Sumarna, Gian (Jurnal Manajemen dan Bisnis, 2026)
The focus of this research is to find and analyze the magnitude of the influence of customer experience on repeat purchases at Mihar Store Pandeglang with online brand communities and positive electronic word of mouth as mediating variables. The type of this research is quantitative. The research population consists of consumers of Mihar Store products in Pandeglang. The sample size was determined using the Roscoe method. This research has 24 indicators, so the sample size = 5 x the number of indicators, resulting in 120 samples. Data collection techniques use questionnaires; data analysis techniques use structural equation modeling (SEM) and partial least square path analysis. (PLS). The results of this study indicate that, partially, customer experience, online brand communities, and positive electronic word of mouth have a positive and significant effect on product repurchase; customer experience has a positive and significant effect on online brand communities; customer experience has a positive and significant effect on positive electronic word of mouth; and online brand communities and positive electronic word of mouth mediate the effect of customer experience on product repurchase